ASUHAN KEPERAWATAN KETIDAKSTABILAN GLUKOSA DARAH PADA PASIEN TN. D DENGAN DIABETES MELITUS TIPE II DI RSI BANJARNEGARA - Han Adam Renaldi; Amin Susanto; Asmat Burhan (Sekolah Tinggi Pariwisata Mataram, 2022)
Diabetes mellitus is a metabolic disorder characterized by high sugar levels associated with abnormal carbohydrate, fat, and protein metabolism caused by decreased insulin secretion or decreased insulin sensitivity effectively. One of the nursing problems that always arise in people with Diabetes Mellitus is the risk of unstable blood glucose levels. Ignorance of diet is one of the efforts to achieve treatment goals in type 2 diabetes mellitus patients. Therefore, health education is needed for type 2 DM patients. The author's aim is to provide nursing care for blood glucose instability in Mr D with Type II Diabetes Mellitus. Actions by providing implementation The implementation of nursing care actions carried out is conducting a diet therapy program for clients which is carried out for 3 days, accompanied by daily GDS measurements. Education is education or training regarding knowledge and skills in the management of diabetes mellitus given to every patient with diabetes mellitus. Providing education includes basic knowledge about diabetes mellitus, meal planning, physical activities and foot care